Pulmonary MALT lymphoma diagnosed with transbronchial lung cryobiopsy after unsuccessful transbronchial lung biopsy: a case report - Tsukada, Akinari; Suzuki, Manabu; Misumi, Kento; Miyazaki, Hideki; Igari, Toru; Takasaki, Jin; Nishimura, Naoki; Nokihara, Hiroshi; Izumi, Shinyu; Hojo, Masayuki (Frontiers in Medicine, 2025)
Primary pulmonary mucosa-associated lymphoid tissue (MALT) lymphoma is a rare primary lung neoplasm and a low-grade B-cell non-Hodgkin lymphoma subtype. Although the prognosis is generally favorable, nonsurgical biopsy methods often have a low diagnostic yield, leaving the optimal approach for pulmonary lesion biopsy unclear. This case study illustrates the successful diagnosis of pulmonary MALT lymphoma using transbronchial lung cryobiopsy (TBLC) after usual transbronchial lung biopsy (TBLB) failed to provide a definitive diagnosis. A 47-year-old female with no significant medical history was referred to our institution after a chest radiograph revealed abnormalities. Subsequent chest computed tomography showed tumorous lesions measuring 20 mm in the right middle lobe and 35 mm in the left lower lobe, prompting a bronchoscopic examination. Guided sheath transbronchial lung biopsy (GS-TBLB) was performed on these two lesions, revealing CD20-positive lymphocytic infiltration. However, the lack of a clear light chain restriction and minimal plasma cell differentiation did not suggest malignant lymphoma. Considering cryptogenic organizing pneumonia, prednisolone was administered for 3 months, but no changes in radiographic findings were observed. Therefore, a second bronchoscopic examination using TBLC was planned. TBLC was performed twice on the left lower lobe lesion, revealing diffuse infiltration of small lymphoid cells into the lung parenchyma and subepithelial bronchial tissue, with some cells differentiating into plasma cells. In situ hybridization showed λ dominant light chain restriction, confirming the diagnosis of MALT lymphoma. The patient, asymptomatic and with no evidence of tumor cell infiltration into the bone marrow, continued to be observed. Pulmonary MALT lymphoma has a favorable prognosis and less invasive diagnostic approaches are desirable. However, conventional TBLB has a low diagnostic yield, suggesting the potential utility of TBLC in diagnosis.